Application of Fuzzy Mamdani Method in the Determination of Total Production - Arifah, Enny Durratul; Irawan, Mohammad Isa; Mukhlash, Imam (Jurusan Matematika FMIPA Universitas Jember, 2017)
There are many ways to determine total of production, one of them is by using fuzzy logic. At the research was used fuzzy inference method Mamdani model. The design of the system to get the output done in several stages namely: [1] the formation of fuzzy sets, [2] the implications of the application function, (3) establish the rules-the rules, [4] defuzzyfication. In this research, defuzzyfication is performed using Composite Moment (centroid) method. With this system expected to be made to assist companies in making decisions to determine the number of production must be producted every month to warehouse inventory remained stable.